The predictive value of maternal serum screening tests for adverse pregnancy outcomes (Annals of Medical Research, 2021)
Aim: Free beta-human chorionic gonadotropin (Fβ-hCG), pregnancy-associated plasma protein-A (PAPP-A), alpha-fetoprotein (AFP), unconjugated estriol (uE3), and inhibin-A have been shown to be useful not only in identifying chromosomal abnormalities in the first and second trimesters, but also in predicting adverse pregnancy outcomes (APOs). In this study, we aimed to investigate the predictive value of maternal serum screening tests for various APOs including preeclampsia, intrauterine growth retardation (IUGR), preterm labor, and gestational diabetes mellitus (GDM).Material and Methods: The study was carried out at our clinics and included a total of 220 pregnant women who respectively underwent the double and quadruple marker testsduring the 11th to 14th and 15th to 22nd gestational weeksbetween January 2017 and December 2018. Patient data (maternal age, parity/gravidity, gestational age, history of infertility, use of in vitro fertilization, maternal/fetal complications, preterm labor, mode of delivery, birth weight, and length of stay in the neonatal intensive care unit) were reviewed retrospectively.Results: The AFP levels were statistically significantly higher in patients with IUGR (p=0.022),GDM (p=0.036), and preterm labor (p=0.021), compared to the control group with no APO. No significant correlation was found between preeclampsia and the serum markers.Conclusion: Our results show that elevated maternal serum AFP levels might be associated with various APOs,requiring closer patient follow-up for early diagnosis and treatment.